HemoCue photometer: a better alternative of hemoglobin estimation in blood donors? - Akhtar, Kafil (Springer-Verlag, 2009)
PURPOSE OF STUDY: To find out the prevalence of anemia in potential blood donors and to compare the direct cynmethemoglobin and HemoCue methods for assessing hemoglobin concentration. MATERIAL AND METHODS: The study group included 540 potential blood donors; who were tested for their hemoglobin concentration in capillary blood samples by direct cynmethemoglobin and HemoCue methods. RESULTS: Average age of the potential donors was 39.2 year, with 505 males and 35 females. Mean hemoglobin concentration using the HemoCue was 13.2 ± 2.4 g/dl and 12.8 ± 2.3 g/dl with the direct cynmethemoglobin method (Table 1). The prevalence of anemia was slightly higher when using the direct cynmethemoglobin method (14.1%) as compared to HemoCue method (13.6%). The sensitivity and specificity for the HemoCue assessment was 94.1% and 95.2% respectively as compared to 90.1% and 94.2% respectively for the direct cynmethemoglobin method. CONCLUSION: Photometric hemoglobin determination (HemoCue) combines the convenience of onsite testing with sufficient accuracy and rapidity. We feel this is a better method for evaluating potential blood donors.